The insertion of the nurse midwife in delivery and birth: obstacles in a teaching hospital in the Rio de Janeiro state - Rosangela da Conceição Sant'anna Amaral; Valdecyr Herdy Alves; Audrey Vidal Pereira; Diego Pereira Rodrigues; Luana Asturiano da Silva; Giovanna Rosário Soanno Marchiori (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: analyze the insertion of the nurse midwife in a teaching hospital in Rio de Janeiro State. Method: descriptive, exploratory study of qualitative nature, study case type, carried out in a maternity in the mountain region, with nine healthcare professionals and six managers. The data collection occurred from December 2016 to March 2017, by semi-structured interviews that subsequently transcribed and submitted to content analysis in the thematic modality. Results: difficulties were observed for the insertion of the nurse midwife such as: lack of specialist nurses in the delivery room; absence of space for the professional autonomy; political partisans influence in the health management; acting conflict with the obstetricians; no team support, mainly with regard to workers qualification. Conclusion: this study shows the need for direct insertion of the nurse midwife in delivery and birth, especially valuing humanized care and autonomy for professional practice.